Gender Mainstreaming in a Teacher Education Institution in the Philippines - Valencia, Minda I. Cabilao (EDUCARE, 2017)
ABSTRACT: This study aims to examine the gender mainstreaming efforts of the PNU (Philippine Normal University), a TEI (Teacher Education Institution) in the Philippines. It specifically looks at the experiences, challenges, and issues of PNU as it implements its gender policies and programs. Using the GMEF (Gender Mainstreaming Evaluation Framework), a gender analysis tool, the study examines the PNUâs GaD (Gender and Development) policy, enabling mechanisms, and gender projects, programs and activities. Data were gathered and analyzed through interviews with concerned university officers and personnel, faculty members, and students. A documentary analysis was also done with the GaD plans, budget, and accomplishment reports of the university, among others. The findings of this investigation show that PNU has been in the forefront of gender mainstreaming activities for several decades. Advanced works have been conducted in different areas of gender mainstreaming. The strength of the policies lies on the management pronouncements in support of gender activities, offering of a Womenâs Studies Program, issuance of an anti-sexual harassment policy, establishment of the UGDO (University Gender and Development Office), and creation of the GaD Focal Point Committee, among others. In addition, the universityâs GaD programs, projects and activities are reflected in its three main functions, namely: instruction, research, and extension. It is hoped that the findings of this study will serve as a guide in assessing the gender policies and programs of other education institutions and other organizations. KEY WORDS: Gender Mainstreaming; Evaluation Framework; Gender and Development; Philippine Normal University; Gender Policies and Programs.About the Author: Minda I. Cabilao Valencia is an Associate Professor of Sociology/Anthropology; former Head of the University Gender and Development Office in PNU (Philippine Normal University); and a member of the NGDRP (National Gender and Development Resource Pool) of the Philippine Commission on Women. E-mail address: valencia.mc@pnu.edu.phHow to cite this article? Valencia, Minda I. Cabilao. (2017). âGender Mainstreaming in a Teacher Education Institution in the Philippinesâ in EDUCARE: International Journal for Educational Studies, Vol.9(2), February, pp.85-94. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-7877. Chronicle of the article: Accepted (October 9, 2016); Revised (January 10, 2017); and Published (February 27, 2017).